THE PARADISE IN WILDERNESS: AN EXEGETICAL APPROACH ON MARK 1:9-13 AND ITS SIGNIFICANCE IN CONTEMPORARY SOCIETIES - Jack Kawira (STTRII, 2016)
Adam brings humanity from paradise to wilderness by his disobedience toward God. Since then, humanity endures countless sufferings in this world and eternal damnation because of sin. But Christ as the second Adam brings himself from paradise to wilderness in order to bring his people from wilderness to paradise by his perfect obedience. Since then, his people not only have the assurance of eternal salvation but also have the possibilities to exercise paradise in the wilderness with Him. Even more, by the power of the Holy Spirit, his people will accomplish their calling as disciples by witnessing paradise in the wilderness contemporary societies to point them to Christ. An exegetical approach on Mark 1:9-13 gives us a strong foundation to discuss the nature of wilderness and its challenges, followed by the Paradise motive which is exclusive to Mark. The significance of the discussion will bring light to explain why so many prophets and apostles exercise real joy in the face of great suffering and tribulation. And of course, from the discussion it is also true for his people in the present and future to exercise or even more to bring paradise into the wilderness by the grace of God.